Safety in public spaces for children's play and learning. (March 2015) - Senda, Mitsuru
Abstract: With societal changes in recent years, issues related to child safety in public places have become more diverse and more complex. Every age has its hardships, and an environment in which children develop into people who overcome such hardships is necessarily one that is not completely free of danger. Nevertheless, there is tendency toward an excessive emphasis on safety. The children of today have been driven indoors, deprived of spaces for group play and of natural environments that encourage a diversity of experience. The development of IT media has further reinforced this tendency. These conditions can be said to produce bullying, abuse, isolation, and a lack of ambition. It is critical that children's living environments, especially public spaces for playing and learning, have a porous structure with numerous routes of escape. Highlights: Most children's accidents involve falling down, so the condition of the floor or ground surface is important. Dangers can be either latent or evident. Maintenance is of fundamental importance in eliminating latent dangers. Dangers include both risks and hazards, which interrelate in the occurrence of accidents. Experiencing little accidents is an important part of learning how to avoid getting caught up in big accidents. Porous spaces conducive to play—those following a circular play structure—are effective spaces for learning safety.